Agentes Etiológicos asociados a enfermedad Diarreica Aguda en niños menores de cinco años atendidos en el hospital de apoyo I Banda de Shilcayo. Noviembre 2002·Abril 2003 - Flores Pinedo, Iris Katiuska (2003)
Flowers Pinedo, lris Katiuska. Etiologic agents associated with acute diarrheal disease in children under five years of age at the Hospital de Apoyo I Band of Shilcayo, National University of San Martín Thesis 2003 A simple descriptive study of a prospective cross-sectional study was carried out to identify the most frequent etiologic agents associated with acute diarrheal disease (EDA) in children under five years of age, and in the support hospital I Band of Shilcayo in the study months . The study population consisted of 126 diarrheal samples of children under five years old who were studied for the search of parasites and enterobacteria. Samples were analyzed by direct examinations for the identification of parasites, while the bacteria were identified on the basis of Their morphological and biochemical cultural characteristics The most frequent etiological agents associated with EDAS in children under five years old attended at the Hospital of Support I Banda da Shilcayo were the parasites 37.3%. Bacteria 26% Parasites and Bacteria 9.5%. The most frequent parasites associated with EDA in children under five years of age were Giardia lamblia 23.2%, with an incidence rate of 17.5%, Cryptosporidium parvum 14.7% representing an incidence rate of 11.1%, Blastocystis hominis 13.7% with An incidence rate of (10.3%) Entamoeba coli 11.6% showed an incidence rate of (8.7%) The most frequent isolated bacteria associated with EDA in children under five years were: Proteus mirabilis 28.3% with an incidence rate of (10.3%). Klebsiella sp 26.1% establishing an Incidence slice (9.5%). Serratia marcscences 17.4% represents an incidence rate of (6.3%). The incidence rate of acute diarrheal disease in the study period was (11.3%) There is no relationship between the type of etiological agent and the types of EDA according to the study are independent because the calculated chi square is smaller (14.2) than The chi square tabulated (16.9)